Topological Acoustic Sensing Using Nonseparable Superpositions of Acoustic Waves - Trevor D. Lata; Pierre A. Deymier; Keith Runge; William Clark (Vibration, 2022)
We introduce a method, topological acoustic sensing, which exploits changes in the geometric phase of nonseparable coherent superpositions of acoustic waves to sense mass defects in arrays of coupled acoustic waveguides. Theoretical models and experimental results shed light on the origin of the behavior and sensitivity of the geometric phase due to the presence of mass defects. The choice of the coherent superposition of waves used to probe the defects as well as the mathematical representation determining the topological characteristics of its space of states are shown to be critical in maximizing the sensitivity of the topological acoustic sensing method.